Movimentos imagem - Priscila Mesquita Musa (2015)
On the scale of ordinary life, up to the eye, the city is conditioned, not submissive, to relations of power and centripetal forces from public institutions, economic power, political power, social power, media power but the city is also what escapes from these forces, what remains, what goes out, what does not reach us. Even in the most inhospitable, hard and inhumane conditions, there are some pieces of city that resist in the power of its cracks. There is something which is able to break time, space and body planning and then institute other cities. That's the greater power of some occupation movements in public space, aiming to create breaks in the city spacetime. This whork is a reflection on the production and circulation of images of collective movements in public space of Belo Horizonte. It was developed from the experience with a few movements and groups, sharing photos and videos and from the collective construction of research through conversation circles. It is an investigation of the expressive power of the image as destabilizing spaces and times socially established and its ability to redistribute the sensitive, from the analysis of the relationship between its agents c photographer, photographed, spectator and camera.